The Intel microprocessors : 8086/8088, 80186, 80286, 80386, and 80486 architecture, programming, and interfacing - Brey, Barry B. (New York : Macmillan Publishing Company, 1991)
This edition begins with an overview of the 8086/8088 microprocessor family and coverage of the instruction set along with its diverse addressing modes. The 8086/8088 instructions set and hardware principles are upward compatible to the 80186/80188, 80286, 80386, and 80486 microprocessors.
1: Introduction to the 8086/8088 Microprocessor -- 2: Addressing Modes -- 3: Data Movement Instructions -- 4: Arithmetic and Logic -- 5: Program Control Instructions -- 6: 8086/8088 Hardware Specifications -- 7: Memory Interface -- 8: Basic I/O Interface -- 9: Interrupts -- 10: Direct Memory Access -- 11: The 8087 family of arithmetic coprocessors -- 12: The 80186, 80188, and 80286 Microprocessors -- 13: The 80386 and 80486 Microprocessors -- Appendixes -- Index.
Includes index.
Keywords: INTEL 8086 (MICROPROCESSOR)